2023
DOI: 10.23923/rpye2023.01.229
|View full text |Cite
|
Sign up to set email alerts
|

Estrés en tiempos de confinamiento: estrategias de afrontamiento y crecimiento postraumático en población universitaria.

Abstract: Background: Recently, the appearance of the SARS CoV-2 virus caused university students to experience cessation of their academic activity while they were subjected to mandatory confinement (exceptional situation). The objective of the present retrospective study was to analyze stress, anxiety, and depression levels in university students in the period from March to May 2020, as well as to evaluate their coping strategies and the post-traumatic growth experienced. Method: A total of 239 students took part in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…Apart from this review undertaken by Cochrane (Kunzler et al, 2020), other studies also indicate that these factors may impact the strengthening of resilience and post-traumatic growth (Chi et al, 2020;Hernández-Ballester et al, 2023) in students in the area of health. These factors could be explored in longitudinal studies once the health emergency has ended.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from this review undertaken by Cochrane (Kunzler et al, 2020), other studies also indicate that these factors may impact the strengthening of resilience and post-traumatic growth (Chi et al, 2020;Hernández-Ballester et al, 2023) in students in the area of health. These factors could be explored in longitudinal studies once the health emergency has ended.…”
Section: Discussionmentioning
confidence: 99%
“…Within the framework of the COVID-19 pandemic, resilience has been shown to play a protective role with regard to mental health disorders (PeConga et al, 2020;Yildirim & Solmaz, 2022). Regarding its levels, studies have shown that they can remain stable (Castagnola Sánchez, Cotrina-Aliaga, & Aguinaga-Villegas, 2021), increase (Hernández-Ballester, Ferrer-Pérez, Montagud-Romero, & Blanco-Gandía, 2023), or be affected by alterations related to COVID-19 (Delgado, 2020;Killgore, Taylor, Cloonan, & Dailey, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, it is often more time-consuming for vocational students to regulate their stress in certain academic situations during the internship period ( Schulten and Wussler, 2013 ). The use of different coping strategies will explain individual differences in relation to adapting to the stress required by these new educational demands ( Hernández et al, 2023 ). See Figure 1 to visualise the hypothetical model of relationships that we will describe below.…”
Section: Introductionmentioning
confidence: 99%
“…Los estudiantes universitarios enfrentan nuevos retos que se experimentan como estresantes tanto a nivel individual, familiar y académico, tal es el caso del manejo de tiempo o el periodo de exámenes, que, sumado a la sobre carga académica, la realización de prácticas, la competitividad, las exigencias académicas y la influencia del entorno, puede derivar en problemas de salud tanto física como mental, ejemplo de ello son la irritabilidad o ansiedad, lo anterior a causa del continuo estrés al que se ven sometidos (Hernández-Ballester et al, 2023;Mur et al, 2023;Rodríguez-Fernández et al, 2020).…”
Section: Introductionunclassified
“…Todos los estudiantes universitarios experimentan estrés de forma cotidiana, pero dicha experiencia no es idéntica para todos, ya que las reacciones que tienen ante el estrés varían debido a las estrategias que tienen de forma personal para hacerle frente; dichas estrategias de afrontamiento son herramientas que permitirán una autorregulación a nivel emocional, cognitiva, conductual, así como la adaptación ante situaciones estresantes (Fuster-Guillén et al, 2021;Hernández-Ballester et al, 2023).…”
Section: Introductionunclassified